2021
DOI: 10.1186/s12877-021-02305-8
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling is as important as multiple previous falls in terms of limiting daily activities: a longitudinal study

Abstract: Background Fear of falling and previous falls are both risk factors that affect daily activities of older adults. However, it remains unclear whether they independently limit daily activities accounting for each other. Methods We used the data from Round 1 (Year 1) to Round 5 (Year 5) of the National Health and Aging Trends Study. We included a total of 864 community-dwelling participants who provided data on previous falls, fear of falling and lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 38 publications
1
39
1
2
Order By: Relevance
“…A systematic review has shown that individuals with FoF have more than double the risk of falling than those without FoF [ 6 ]. Additionally, some studies reveal that FoF is associated with various changes, which increase the risk of falls (e.g., inappropriate attention allocation, fixed vision trajectory, and an inactive lifestyle) [ 7 9 ]. Considering the strong association between FoF and occurrence of falls, it is important for health-related workers in the community to obtain FoF information.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review has shown that individuals with FoF have more than double the risk of falling than those without FoF [ 6 ]. Additionally, some studies reveal that FoF is associated with various changes, which increase the risk of falls (e.g., inappropriate attention allocation, fixed vision trajectory, and an inactive lifestyle) [ 7 9 ]. Considering the strong association between FoF and occurrence of falls, it is important for health-related workers in the community to obtain FoF information.…”
Section: Introductionmentioning
confidence: 99%
“…As described above, only few studies have investigated the persistent or/and transient nature of FoF in older CD persons already having experienced a fall or injurious fall in a longitudinal study design [ 2 , 11 ]. One might speculate that over time the detrimental experience of a fall could be reduced and that FoF could also decrease or even disappear.…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocially, falls may cause fear of falling, which is a relevant fall risk factor itself, with prevalence ranging between 30 to 73% [ 12 , 13 ]. Fear of falling may result in reduced physical activity [ 14 ], and affect social participation, thus, increasing the risk of social isolation and loss of independence [ 15 , 16 ]. Therefore, the manifold consequences of falls do not only impair quality of life, but also increase the risk of further diseases and disorders such as depression and dementia [ 16 18 ], potentially forming a vicious circle.…”
Section: Introductionmentioning
confidence: 99%